Survival outcomes in pediatric recurrent high-grade glioma: results of a 20-year systematic review and meta-analysis - Kline, Cassie (J Neurooncol, 2017)
Recurrent pediatric high-grade glioma is a leading cause of cancer-related death in children. We report results of a systematic review and meta-analysis investigating survival outcome in pediatric patients with recurrent high-grade glioma over the last 20 years. METHODS: MEDLINE/PubMed, EMBASE, Web of Science and Cochrane Review databases were searched for relevant studies reporting on survival outcomes for pediatric patients with recurrent high-grade glioma treated between 1996–2016. Progression-free survival (PFS) and overall survival (OS) were calculated cumulatively over all studies, by therapy subgroup, and by decade of treatment. Random effects models were used to control for heterogeneity as measured by the I(2) statistic. RESULTS: A total of 17 studies across 4 treatment strategies were included. Eleven investigated traditional chemotherapy, 1 investigated targeted therapy, 3 investigated immunotherapy, and 2 investigated radiotherapy. A total of 129 patients were included with a median age of 10.0 years. Cumulative PFS was 3.5 months (95% CI 2.1, 5.0). Cumulative OS was 5.6 months (95% CI 3.9, 7.3). OS was 4.0 months (95% CI 1.9, 6.1) using traditional chemotherapy, 9.3 months using targeted therapies (95% CI 5.4, 13), 6.9 months using immunotherapy (95% CI 2.1, 12), and 14 months using reirradiation (95% CI 2.8, 25). OS between 1996 and 2006 was 4.2 months (95% CI 2.1, 6.2) compared to 8.5 months (95% CI 5.6, 11) after 2006. CONCLUSIONS: Pediatric patients with recurrent high-grade glioma suffer from poor PFS and OS, regardless of therapy. There may be a trend towards improved OS in the last decade.